2021
DOI: 10.1177/0963689721993774
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing by Allogeneic Transplantation of Specific Subpopulation From Human Umbilical Cord Mesenchymal Stem Cells

Abstract: In normal physiological conditions, restoration of a functional epidermal barrier is highly efficient; nevertheless, when it fails, one of the main consequences is a chronic ulcerative skin defect, one of the most frequently recognized complications of diabetes. Most of these chronic venous ulcers do not heal with conventional treatment, leading to the appearance of infections and complications in the patient. Treatments based on the use of autologous mesenchymal stem cells (MSC) have been successful; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…[ 24 ] Second, CD29 was identified as another one of the candidate gene, as it is essential for wound healing, re‐epithelialization and vascularization [ 25 ] and has been shown to be a highly expressed gene of the MSC subpopulation beneficial to wound repair. [ 26 ] CD142 + WJ‐MSCs also have potential for wound repair. [ 11a ] Finally, based on comprehensive analysis of single‐cell data, gene function data and subcellular localization data, as well as a literature review, we identified CD142, CD29 and S100A9 as the candidate marker genes of this subpopulation for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] Second, CD29 was identified as another one of the candidate gene, as it is essential for wound healing, re‐epithelialization and vascularization [ 25 ] and has been shown to be a highly expressed gene of the MSC subpopulation beneficial to wound repair. [ 26 ] CD142 + WJ‐MSCs also have potential for wound repair. [ 11a ] Finally, based on comprehensive analysis of single‐cell data, gene function data and subcellular localization data, as well as a literature review, we identified CD142, CD29 and S100A9 as the candidate marker genes of this subpopulation for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…UCMSCs have received recent attention due to their powerful regenerative and immunomodulatory potential, and their EVs provide an emerging role in modulating the symptoms of various diseases ( Hollweck et al., 2012 ; Monguio-Tortajada et al., 2017 ; Lv et al., 2020 ; Liu et al., 2021 ; Palma et al., 2021 ). A recent study reported that co-culturing UCMSCs with IFV A/H5N1-infected alveolar epithelial cells significantly restored alveolar fluid clearance and protein permeability through the secretion of angiopoietin-1 and hepatocyte growth factor, factors which promote angiogenesis and cell growth and survival, respectively ( Loy et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, UCMSCs are known for their immunosuppressive properties including low expression of major histocompatibility complex class I molecule and costimulatory factors such as CD80 and CD86 ( Tipnis et al., 2010 ). Recent studies indicate that exosomes derived from UCMSCs (U-exo) have a significant role in immune modulation, tissue regeneration and antimicrobial defense by directly modulating immune response and enhancing the proliferative potential of tissues ( Hollweck et al., 2012 ; Monguio-Tortajada et al., 2017 ; Lv et al., 2020 ; Liu et al., 2021 ; Palma et al., 2021 ). However, the role of U-exo on respiratory viral infection and pathogenesis has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, The rejection of transplanted allogeneic ECSs may not be observed within a week after the transplantation of allogeneic ECSs. In clinical settings, allogeneic tissue-engineered skin therapies provide biological dressings, matrix materials, cytokines, and regulatory molecules to maintain a suitable environment for wound healing without any immunological problems [ 50 , 51 ]. Moreover, the risk of immunological rejection can be minimized if the cell source for transplantation can be selected from a cell bank based on the human leukocyte antigen matching score, as in haplotype-based banking of human pluripotent stem cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%